ICT, responsibility and human development in Venezuela. Generalities about their relationship and constitutional and legal foundations (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
Both human activities and their relationships are focused on information and knowledge revolution. Information Technology and Communication (ICT) is their solid ground. Science, technology, innovation activities, applications and use of results, should contribute to the welfare of humanity, poverty reduction, respect for dignity, human rights and environment preservation in order to ensure human development. Venezuelan National System of Science, Technology and Innovation, is expected to build capacity for younger generations, use and make circulate knowledge and promote national development. This qualitative research examined ICT, its accountability and relationship to Venezuela human development, in order to build a theoretical approach in response to hermeneutic interpretation documents and constitutional and legal provisions in force. It was concluded that a link is encouraged among information technology and communication to human development and accountability as a constitutional principle through various existing regulatory bodies relevant to these issues.
Keywords: information and communications technologies; responsibility; human development